2018
DOI: 10.18632/oncotarget.24528
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed procyanidin extract against lung cancer: the role of microrna-106b, bioavailability, and bioactivity

Abstract: MiR-106b is an oncomir and a potential target for anti-cancer therapy. We hypothesize that grape seed procyanidin extract (GSE) exerts antineoplastic effects on lung cancer through modulations of miR-106b and its downstream target. We found that GSE significantly down-regulated miR-106b in a variety of lung neoplastic cells and increased cyclin-dependent kinase inhibitor 1A (CDKN1A) mRNA and protein (p21) levels. Transfection of miR-106b mimics reversed the up-regulations of CDKN1A mRNA and p21, abrogated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…To assess bioavailability, GSE and metabolites in plasma levels were measured at weeks 4 and 8 of treatment 60–90 min after the LP probe. The findings show new antineoplastic mechanisms of GSE, further define the pharmacokinetics and pharmacodynamics of LP, and support further research on the use of LP against lung cancer [ 52 ].…”
Section: Studies Related To Oncological Diseasessupporting
confidence: 57%
See 1 more Smart Citation
“…To assess bioavailability, GSE and metabolites in plasma levels were measured at weeks 4 and 8 of treatment 60–90 min after the LP probe. The findings show new antineoplastic mechanisms of GSE, further define the pharmacokinetics and pharmacodynamics of LP, and support further research on the use of LP against lung cancer [ 52 ].…”
Section: Studies Related To Oncological Diseasessupporting
confidence: 57%
“…A study conducted by Xue et al [ 52 ] tested the effect of grape procyanidin extract against lung cancer, and its bioavailability and bioactivity. MiR-106b is a potential target for antitumor therapy.…”
Section: Studies Related To Oncological Diseasesmentioning
confidence: 99%
“…Resveratrol is a polyhydric phenolic compound. In addition to preventing cardiovascular and cerebrovascular diseases, it also has strong anticancer abilities [28]. Some clinical data have shown that procyanidin oligomers from grape seeds are 20 times more potent than vitamin C and 50 times more potent than vitamin E in antioxidants [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that polyphenolic and gallic acid contents of GSE have a role in scavenging free radicals which possess varieties of valuable health effects (Abhijit et al, ; Frankel, German, Kinsella, Parks, & Kanner, ; Jorge, Ricardo Da Silva, Fernandez, & Mitjavila, ; Safaei et al, ; Shi et al, ; Xue, Lu, Massie, Qualls, & Mao, ). It seems that obesity‐related inflammation is also associated with higher level of oxidative stress (Fernández‐Sánchez et al, ).…”
Section: Discussionmentioning
confidence: 99%